Detecting Initialization Bias in Simulation Output - Schruben, Lee W. (Operations Research, 1982)
A general approach to testing for initialization bias in the mean of a simulation output series is presented. The output is transformed into a standardized test sequence that can be contrasted with a known limiting stochastic process. This transformation requires very little computation and the asymptotic theory is applicable to a wide variety of simulations. An initialization bias test is developed and several examples of its application are presented.